Geothermal based hybrid energy systems, toward eco-friendly energy approaches. (March 2020) - Olabi, Abdul Ghani; Mahmoud, Montaser; Soudan, Bassel; Wilberforce, Tabbi; Ramadan, Mohamad
Abstract: Geothermal Energy is a very attractive source of naturally-occurring green renewable energy. Exploiting this natural resource is straightforward and causes almost no ill effects to the environment. But, while geothermal does not suffer the intermittence of other renewable sources, its extraction efficiency is fairly modest as compared to other sources. As a result, there has been significant interest recently in hybrid systems that integrate geothermal and other forms of energy to increase the output efficiency. This work will survey the different possible integrations involving geothermal energy. A review of the literature shows that the most common hybrid systems implementation involve the integration of geothermal with solar (45% of systems) followed by the integration of a cooling tower into the geothermal system (30% of systems). This work will also investigate the applications for geothermal hybrids and show that 44% of systems are designed for heating applications. Another 44% are used for cooling while only 12% are designed for electrical power generation. Complexity of control remains as the main obstacle facing hybrid multi-source energy systems including those involving geothermal energy. Graphical abstract: Image 1 Highlights: Hybrid geothermal systems (HGS) have low initial and operating costs. HGSs can supply all types of energy demands and decrease the effect of peak loads. HGSs reduce negative environmental impact of energy systems.